(untitled) (Journal of Hama University, 2022)
The Corona pandemic has affected all aspects of economic life worldwide with a clear impact on international financial markets. This study endeavors to examine the impact of Covid-19 on the volatility of Damascus Securities Exchange (DSE) Index where volatility is measured according to S&P simple-weighted volatility method. Authors use a number of GARCH models to explore the impact of Covid-19 on index volatility. This study finds that DSE has witnessed unprecedented volatility during the lockdown and that the governmental rules have contributed towards the continuity of the upward trend in DSE index but they failed to control its volatility. This study recommends the management of DSE to develop an index for stock market volatility and use it as an early warning system to anticipate uncertainty in the stock market and to enable regulators to take suitable precautionary measures. It also suggests offering stimulation packages to counteract the impact of Covid-19 on the economy and financial market.